2019
DOI: 10.1186/s12859-019-2952-9
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of autoencoders to learn biological regulatory modules from single cell mRNA sequencing data

Abstract: Background: Unsupervised machine learning methods (deep learning) have shown their usefulness with noisy single cell mRNA-sequencing data (scRNA-seq), where the models generalize well, despite the zero-inflation of the data. A class of neural networks, namely autoencoders, has been useful for denoising of single cell data, imputation of missing values and dimensionality reduction. Results: Here, we present a striking feature with the potential to greatly increase the usability of autoencoders: With specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…For example, autoencoders are a neural network architecture currently used to infer a latent representation of the mRNA transcription patterns obtained from both bulk and single-cell samples 27 , 28 . This representation can be used as a regulatory barcode to generate gene function prediction scores within a GBA strategy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, autoencoders are a neural network architecture currently used to infer a latent representation of the mRNA transcription patterns obtained from both bulk and single-cell samples 27 , 28 . This representation can be used as a regulatory barcode to generate gene function prediction scores within a GBA strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the deep learning method can not only remove the batch effect in the scRNA‐seq data, or complete the clustering of cells, but also directly learn the inherent biological modules in the data, and then describe the biologically meaningful control data set modules and provide information about which modules are active for each unit. For example, the autoencoder after deconvolution processing, 42 it also has good adaptability to a large amount of “lost” data, which is useful and important for analyzing scRNA‐seq data. Kinalis et al found that after specific training, the autoencoder can establish a connection between the model's presentation layer and biological functions after deconvolution of the resulting model.…”
Section: Discussionmentioning
confidence: 99%
“…Kinalis et al found that after specific training, the autoencoder can establish a connection between the model's presentation layer and biological functions after deconvolution of the resulting model. The hidden cells in the model are then mapped to well‐defined modules to complete the signature decryption of genes or locations, so that the autoencoder can better outline the driving factors behind a given cellular effect 42 . This will analyze the stem cell population from another angle, which will help us to screen the subpopulations of stem cells we need, and it will also play a role in promoting the development of stem cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, it should also be possible to combine encodings of the cells in the latent space and produce in-between cells like Lotfollahi et al (2018). We would also like to extent our investigation of what dimensions of the latent variables encode (Kinalis et al, 2019). We note that it is possible to apply these models to data sets with multiple modalities such as RNA-seq and exome sequencing (Brouwer and Lió, 2017).…”
Section: Discussionmentioning
confidence: 99%